Science, capacity building and conservation knowledge: The empowerment of the local community for marine conservation in Rapa Nui. (21st October 2019) - Paredes, Felipe; Flores, Diego; Figueroa, Alejandra; Gaymer, Carlos F.; Aburto, Jaime A.
Abstract: Marine protected areas have been scaling up from small areas located in coastal waters to large‐scale marine protected areas in remote areas, partly in response to the international agenda to conserve 10% of marine and coastal areas. Chile has made considerable progress in the designation of large‐scale marine protected areas in its oceanic islands with varying degrees of top‐down and bottom‐up processes, scientific knowledge and interplay among institutions. The process of designating the multiple‐uses marine protected area in Rapa Nui (Easter Island) involved interplay among scientific research, capacity building, local knowledge and collaboration between sectors, which contributed to the community transformation toward marine conservation in Rapa Nui. A recent increase in scientific research on the marine ecosystems was transmitted to stakeholders and the local community via capacity‐building actions. The knowledge‐based empowerment of the Rapanui population (inhabitants of Rapa Nui) involved the definition not only of the objectives, the extension and the conservation goals of the Rapa Nui multiple‐uses marine protected area, but also of the implications beyond the designation, such as issues of governance, management and financing. The implementation of the Rapa Nui multiple‐uses marine protected area will test local and Rapanui government relationships. The continuous science‐knowledge‐based dialogue in a strengthened relationship between the government and the local community in a 'process of relating' might be the pathway to future effective conservation efforts and successes.